Modified nanostructured metal and metal oxide incorporated reduced graphene-based nanocomposite for electrochemical sensor applications / Marlinda Ab Rahman - Marlinda, Ab Rahman (2017)
The selection and development of an active sensing material is very important in order to sense target analytes for variety of electrochemical sensor. Currently, fabrications of functional nanostructured pave more attention in the sensor nanotechnology. It is due to their high surface-to-volume ratio that plays a key role for an efficient transport of electrons and optical excitation. Thus, the aim of this work is on developing and preparing novel reduced graphene oxide based metal and metal oxide with modified nanostructure materials for electrochemical sensors performance. This research work was divided into three parts. The first part is the synthesis, characterization and fabrication of nitrite sensing consists of flower-like zinc oxide (ZnO) nanostructure and reduced functionalized graphene oxide (rFGO) was prepared via a hydrothermal route. The nanocomposite was deposited on the surface of a glassy carbon electrode and studied using impedance spectroscopy. It exhibits excellent electrocatalytic activity toward the oxidation of nitrite over working potential of 0.9 V (vs. Ag/AgCl), it displayed a higher current and lower over potential (reduced by up to ~200 mV) than controlled electrodes. The amperometric current is linearly related to the concentration of nitrite in the 10 μM to 8 mM range, and the detection limit is 33 μM. The second part of this work is synthetic method for the preparation of reduced graphene oxide–gold nanorods in an aqueous medium for electrochemical sensing of dihydronicotinamide adenine dinucleotide (NADH). The gold nanorods (AuNRs) had an average length of 44 ± 3 nm and a width of 12 ± 2 nm. The electrochemical characteristics of the gold nanorod-reduced graphene oxide/glassy carbon electrode (AuNR-RGO/GCE) were studied using cyclic voltammogram, and the NADH sensing was studied using chronoamperogram. The amperometric current increased linearly when the NADH concentration was increased in the range of 1–31 μM, and the lowest detection limit (LOD) was estimated to be 0.22 μM (S/N = 3). The third part of this work is the preparation of myoglobin-modified gold nanorods incorporating reduced graphene oxide (RGO) were fabricated and deposited on a glassy carbon electrode (GCE) to obtain a sensor for nitric oxide (NO). The AuNRs have an average length of 38 ± 3 nm and a width of 11 ± 1 nm. The GCE modified with the nanohybrid is shown to be a viable sensor for the determination of NO by linear sweep voltammetry. Its electrocatalytic response toward the oxidation of NO is distinctly enhanced compared to other electrodes. The sensor, best operated at a working voltage of 0.85 V (vs. SCE), showed two linear response ranges (from 10 to100 μM, and from 100 to 1000 μM), with a detection limit of 5.5 μM. Furthermore, it exhibits excellent selectivity for NO over common interferents such as NaNO3, and also over electroactive species such as ascorbate, dopamine, glucose, and uric acid. These excellent electrocatalytic properties, wide linear range, low detection limit, high sensitivity, and rapid response time make these modified nanostructures as potential candidate for practical applications.